Study of gravity waves distribution and propagation in the thermosphere of Mars based on MGS, ODY, MRO and MAVEN density measurements. (15th November 2019) - Vals, M.; Spiga, A.; Forget, F.; Millour, E.; Montabone, L.; Lott, F.
Abstract: By measuring the regular oscillations of the density of CO2 in the upper atmosphere (between 120 and 190 km), the mass spectrometer MAVEN/NGIMS (Atmosphere and Volatile EvolutioN/Neutral Gas Ion Mass Spectrometer) reveals the local impact of gravity waves. This yields precious information on the activity of gravity waves and the atmospheric conditions in which they propagate and break. The intensity of gravity waves measured by MAVEN in the upper atmosphere has been shown to be dictated by saturation processes in isothermal conditions. As a result, gravity waves activity is correlated to the evolution of the inverse of the background temperature. Previous data gathered at lower altitudes ( ∼ 95– ∼ 150 km) during aerobraking by the accelerometers on board MGS (Mars Global Surveyor), ODY (Mars Odyssey) and MRO (Mars Reconnaissance Orbiter) are analyzed in the light of those recent findings with MAVEN. The anti-correlation between GW-induced density perturbations and background temperature is plausibly found in the ODY data acquired in the polar regions, but not in the MGS and MRO data. MRO data in polar regions exhibit a correlation between the density perturbations and the Brunt-Väisälä frequency (or, equivalently, static stability), obtained from Global Climate Modeling compiled in the Mars Climate Database. At lower altitude levels (between 100 and 120 km), although wave saturation might still be dominant, isothermal conditions are no longer verified. In this case, theory predicts that the intensity of gravity waves is no more correlated to background temperature, but to static stability. At other latitudes in the three aerobraking datasets, the GW-induced relative density perturbations are correlated with neither inverse temperature nor static stability; in this particular case, this means that the observed activity of gravity waves is not only controlled by saturation, but also by the effects of gravity-wave sources and wind filtering through critical levels. This result highlights the exceptional nature of MAVEN/NGIMS observations which combine both isothermal and saturated conditions contrary to aerobraking measurements. Highlights: Gravity wave activity causes density perturbations in the Martian thermosphere. MAVEN found a correlation between GW activity and inverse background temperature. Lower-altitude aerobraking data do not show this correlation, except for Mars Odyssey. Aerobraking data and GCMs suggest instead wave activity correlated with Static stability. When no such correlation, a mix of saturation, critical levels and sources is suspected.